Capital Budget Implementation in Nigeria: Evidence from the 2012 Capital Budget - Kanayo Kingsley Ogujiuba; Kizito Ehigiamusoe (Contemporary Economics)
The performance of the capital budget has been a subject of debate between the legislative and executive arms of the Nigerian government since 1999. Available statistics suggest that the annual budget has not been able to improve the lives of Nigerians over the past several years because of the weak link between capital budget implementation and poverty reduction, as indicated by the prevailing low index of capture in public expenditures. Using descriptive analysis, this paper examines the capital budget implementation in Nigeria by focusing on the 2012 Federal Government Budget. The findings indicate that only 51% of the total appropriated funds for capital expenditures were utilized as of December 31st, 2012. The observed level of performance is insufficient to foster rapid economic development and reduce poverty. Some of the challenges that are responsible for the low performance include poor conceptualization of the budget, the inadequacy of implementation plans, the non-release or late release of budgeted funds, the lack of budget performance monitoring, the lack of technical capacity among MDAs, and delays in budget passage and enactment. The paper recommends that Nigerian government formulate a realistic and credible budget, release appropriated funds early to Ministries, Departments, and Agencies (MDAs), and strengthen MDAs’ technical capacity to utilize capital expenditures in order to improve the index of capture in public expenditures.